2014
DOI: 10.1371/journal.pone.0090731
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Human Gut Microbiome Composition

Abstract: The composition of the human gut microbiome is influenced by many environmental factors. Diet is thought to be one of the most important determinants, though we have limited understanding of the extent to which dietary fluctuations alter variation in the gut microbiome between individuals. In this study, we examined variation in gut microbiome composition between winter and summer over the course of one year in 60 members of a founder population, the Hutterites. Because of their communal lifestyle, Hutterite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(218 citation statements)
references
References 53 publications
(69 reference statements)
8
191
3
3
Order By: Relevance
“…16S rRNA gene profiling revealed considerable variation of the fecal microbiota composition of the volunteers enrolled in the PROBIOTA-Bb trial, consistent with previous studies (27,28). These interindividual differences support the choice of the crossover design, in which individual participants serve as their own controls, resulting in the reduction of interindividual variation.…”
Section: Discussionsupporting
confidence: 84%
“…16S rRNA gene profiling revealed considerable variation of the fecal microbiota composition of the volunteers enrolled in the PROBIOTA-Bb trial, consistent with previous studies (27,28). These interindividual differences support the choice of the crossover design, in which individual participants serve as their own controls, resulting in the reduction of interindividual variation.…”
Section: Discussionsupporting
confidence: 84%
“…The composition of the bacterial microbiota displays considerable variation by geographic setting [150][151][152], lifestyle [153] and season [154]. As such, the ecological landscape into which an oral vaccine is introduced is likely to vary considerably between infants in high-and low-income countries.…”
Section: The Commensal Microbiotamentioning
confidence: 99%
“…For example, the shotgun metagenome analysis of two healthy adults revealed a significant metabolic enrichment of glycans, amino acids, and xenobiotics; methanogenesis; and 2-methyl-D-erythritol 4-phosphate pathway-mediated biosynthesis of vitamins and isoprenoids in the human gut microbiome. 28 Moreover, the gut microbiota is not constant, and can be altered by diet, 5,6,29 antibiotic usage, 7,8 aging, 30,31 and many other factors. As well as aiding investigation of the relationship between gut microbiota and human health, metagenomic studies have also necessitated a better understanding of the dynamics of gut microbiome.…”
Section: Metagenomics: Toward a Better Understanding Of The Gut Micromentioning
confidence: 99%
“…As well as aiding investigation of the relationship between gut microbiota and human health, metagenomic studies have also necessitated a better understanding of the dynamics of gut microbiome. For instance, Davenport et al 29 found that seasonal differences in diet shape the gut microbiome compositions of Hutterite individuals differently between the winter and summer. Rampelli et al 30 observed an age-related reduction of the abundance of genes involved in short-chain fatty acid (SCFA) production, and identified 116 microbial genes that significantly correlated with aging.…”
Section: Metagenomics: Toward a Better Understanding Of The Gut Micromentioning
confidence: 99%